Penguatan Sistem Pengawasan Keselamatan melalui Pemantau Kerja Terintegrasi secara Digital CCTV dalam Kegiatan Hot Gas Path Inspection - Amin, Makomulamin; Fadila, Fadila; Hanafi, Ahmad; Sohor, Suherman (Jurnal Kesehatan Komunitas, 2025)
Hot Gas Path Inspection (HGPI) is a high-risk work area with a vast working area and a considerable number of crews. The limited availability of HSE personnel, coupled with the expanding work area, underscores the importance of surveillance using CCTV cameras. X utilizes CCTV surveillance to evaluate worker behavior and working conditions in real-time within the Hot Gas Path Inspection area. The objective of this research is to investigate safety surveillance through digital CCTV worker monitoring during Hot Gas Path Inspection activities at the X Power Plant. This research was conducted from April to July 2024. A qualitative research method was employed, involving in-depth interviews with four informants: a Field HSE Specialist, a Supervisor of the Digital CCTV Command Center, a User Team member, and a worker. The research findings indicate that the implemented digital CCTV surveillance system has demonstrated satisfactory performance in supporting the execution of hot gas path inspection activities. Policies, human resources, infrastructure, work procedures, and existing evaluation mechanisms have been well-integrated. To continually enhance the system's effectiveness and efficiency, the company is recommended to conduct comprehensive evaluations periodically, covering technical, operational, and organizational aspects. This is to ensure that the implementation of surveillance technology remains aligned to improve occupational safety and health.